Development and Evaluation of the Person Attuned Musical Interaction (PAMI) in dementia manual- UK version - Waters, Bryony (2024)
Background- People living with dementia in care homes often have difficulty communicating. Person Attuned Musical Interaction (PAMI) is a music therapy skill-sharing training tool originally developed in Denmark that aims to raise staff’s awareness of musical interactions to encourage them to use communication forms that remain accessible to residents with dementia. This study aimed to translate and adapt PAMI for the UK, before evaluating the adapted intervention in UK care homes. Methods – A narrative synthesis systematic review investigated how care home music interventions facilitate social interactions. The results, along with expert consultations with care staff and the Danish team, guided the cultural adaptation of PAMI-UK. PAMI-UK consists of a 3-hour online training webinar, a manual, and fortnightly reflective sessions. For the manual field-testing study five staff-resident dyads from three care homes participated, with PAMI-UK implemented for eight weeks. The manual evaluation study included 19 dyads from four care homes, with PAMI-UK implemented for 18 weeks. Qualitative data included diary entries, post-intervention interviews, reflective session transcripts and resident questionnaires. The evaluation study additionally collected quantitative data using SCIDS, QUALIDEM, MiDAS and M-NCAS. The studies explored the suitability, usability and readability of PAMI-UK and the impact the intervention had on staff and residents. Results – The final PAMI-UK intervention consists of four elements: The Voice explores the musical parameters within the voice including tempo, pitch, and volume. Framing focuses on assessing and altering the care home environment in relation to sounds. Balancing explores resident’s and staff’s arousal and emotional state. Connecting focuses on using music to create meaning interactions. Resulting from the systematic review and expert consultations, the course layout, duration, and training facilitator was altered. Rather than the intervention training music therapists to train care staff, PAMI-UK was culturally adapted for the PAMI-UK team to train care staff directly. The manual field-testing and evaluation studies demonstrated staff successfully implementing all four PAMI-UK elements adapting skills to resident’s needs. Although the manual was well received by staff, the field-testing study highlighted several key areas requiring refinement including providing information on using PAMI-UK in group situations, creating a recap sheet, and reflective prompt sheets. The qualitative analysis showed that staff altered their behaviour, and subsequently, resident behaviour changed. Both staff and residents reported being happier, less stressed, and calmer, which had a positive impact on the care home environment and subsequently improved task efficiency. SCIDS score increased (P=0.04), suggesting that staff felt more competent in caring for residents with dementia. Residents’ tense behaviour also improved (P=0.03). Conclusion - The systematic review, staff consultations, and discussions with the Danish team ensured that the manual was suitable for UK care homes whilst aligning with the original principals and components. PAMI promotes the embedding of person-centred care into residents’ daily lives through music interactions, making residents equal communication partners regardless of their language abilities. Staff demonstrated the development of ‘doing with’ relationships built on independence and the person behind the dementia diagnosis. Both care home studies had high dropout rates and missing data due to the researchers being unable to attend care homes owing to COVID-19 restrictions. The training was delivered remotely to adhere to the COVID-19 guidelines; however, this made it difficult to determine whether the intervention was implemented correctly. Future research is needed that addresses the methodology difficulties such as online delivery, high dropout rates, and lack of persons with dementia perspective. PAMI-UK has the potential to change care home culture, which future studies should explore.